Faktor-faktor Penyebab Mahasiswa Kurang Memanfaatkan Koleksi UPT Perpustakaan Universitas Bung Hatta - Miharti, Isra; Ardoni, Ardoni (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2013)
The purpose of this study was to describe the factors that cause students not to visit Bung Hatta Library. Data was collected through observation and guided interviews.Â Interviews was were given to students.The data was analyzed by (1) describe the results ofthe interview, (2) describe thedirectobservation, (3) obtained in accor dance with the theories discussed, (4) concluded, (5) reporting. Based on analyzing the data it can be concluded: (1) the of the library is very far from the students location studied at campus II Aia Pacah, (2) the collection thatÂ available in the library are obselent and (3) the books which are needed by student are often not available in the library. Bung Hatta University Library should provides a collection as the uders needed. Collections of the library can not meet the needs of the students, and the collection most obselent. Keywords: collection; library